Seeking Allah, finding Jesus : a devout Muslim encounters Christianity - Qureshi, Nabeel (Grand Rapids, MI : Zondervan, 2014)
Qureshi describes his dramatic journey from Islam to Christianity, and shares how he developed a passion for Islam before discovering, almost against his will, evidence that Jesus rose from the dead and claimed to be God-- and of the peace he eventually found in Jesus.
Prologue: Seeking Allah -- Called to prayer -- An ambassador for Islam -- Testing the New Testament -- Coming to the crux -- Jesus: mortal messiah or divine son of God? -- The case for the gospel -- The truth about Muhammad -- The holiness of the Quran -- Faith in doubt -- Guided by the hand of God -- Epilogue.
Includes bibliographical references.
Keywords: Qureshi, Nabeel; Christian converts from Islam -- Biography